Application of online interactive health education in the impression making for biological functional denture restoration in a patient with dentition defects (网络互动式健康教育在1例牙列缺失患者生物功能性义齿修复印模制取中的应用及护理体会) - ZHU Suxia (朱素霞); CHEN Jiahong (陈洁红); QIU Mei (丘媚); HUANG Liying (黄丽英); CHEN Manxia (陈曼霞); DU Qihong (杜绮虹); GUO Cong (郭聪); XIAO Wei (肖炜) (Journal of International Translational Medicine Limited, 2024)
To summarize and report nursing experience of the application of interactive online health education in impression making for biological functional denture restoration in a patient with dentition defects. Nursing staff applied interactive online health education in advance, and provided individual guidance on oral-motor movement in the impression making. As a result, the patient demonstrated excellent cooperation with oral movements during the procedure, leading to optimal impression-taking outcomes and improved clinical efficiency. (本文总结网络互动式健康教育应用于1例牙列缺失患者生物功能性义齿修复印模制取中的护理经验。护理人员通过应用网络互动式健康教育提前进行了沟通和教导, 指导患者掌握印模制取时的口腔功能性配合动作, 有效提高患者配合度和印模制取精度。)